Global public interest in systemic lupus erythematosus: an investigation based on internet search data. (October 2019) - Wu, G C; Cao, F; Shen, H H; Hu, L Q; Hu, Y; Sam, N B
Objective: This study aims at investigating the global public interest in seeking information about systemic lupus erythematosus (SLE) using Google Trends (GT). Methods: An electronic search was performed using GT with the search term lupus as well as the option of disease from January 2004 to December 2018. Cosinor analysis was applied to detect the seasonality of SLE-related relative search volume (RSV). In addition, analysis on SLE-related topics including "hot topics" and "top rising topics" was also conducted. Results: Overall, SLE-related RSV showed a decreasing trend from January 2004 to December 2013 and then demonstrated a slowly increasing trend from January 2014 to December 2018. Cosinor test showed no significant seasonal variation in SLE-related RSV ( p > .025). RSV peaked in May and reached the trough in November. The top seven rising topics were Selena Gomez, Sjögren syndrome, autoimmunity, rheumatoid arthritis, rheumatology, antinuclear antibody and autoimmune disease. Conclusion: The results from GT analysis showed slowly increasing internet searches for SLE in recent years. This trend was followed by a peak of RSV in May and reached its lowest level in November. However, globally, the results did not reveal a significant seasonal variation in GT for SLE. Additionally, the top fast-growing topics regarding SLE may be valuable for doctors and nurses to provide timely education of the disease to patients, as well as promote the development of public health.